Humanity remembers: on Jung, mythological criticism and archetypes - Gimenez, Carolina (2020)
Fil: Gimenez, Carolina. Pontificia Universidad Católica Argentina. Facultad de Filosofía y Letras. Departamento de Lenguas; Argentina